2003
DOI: 10.1001/archsurg.138.5.514
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms Are a Poor Indicator of Reflux Status After Fundoplication for Gastroesophageal Reflux Disease

Abstract: Background: If a patient develops foregut symptoms after a fundoplication, it is assumed that the operation has failed, and acid-reducing medications are often prescribed. Esophageal function tests (manometry and pH monitoring) are seldom performed early in the management of these patients. Hypothesis: In patients who are symptomatic after fundoplication for gastroesophageal reflux disease, a symptom-based diagnosis is not accurate, and esophageal function tests should be performed routinely before starting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 10 publications
1
52
0
5
Order By: Relevance
“…30 Symptoms and antireflux medication after surgery are poor indicators of GERD after fundoplication, because a high proportion of these patients who improve after proton pump inhibitors still have pathologic levels of acid reflux assessed by 24-hour pH monitoring. [31][32][33][34] Bonatti et al have reported as high a proportion as 43% to 62% taking acid suppression medications after fundoplication. [32][33][34][35][36] Lord and others, 36 described that 20 of 86 patients (23%) studied had a positive pH study, 33% of patients with any grade of esophagitis and 46% of these patients presented abnormal fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…30 Symptoms and antireflux medication after surgery are poor indicators of GERD after fundoplication, because a high proportion of these patients who improve after proton pump inhibitors still have pathologic levels of acid reflux assessed by 24-hour pH monitoring. [31][32][33][34] Bonatti et al have reported as high a proportion as 43% to 62% taking acid suppression medications after fundoplication. [32][33][34][35][36] Lord and others, 36 described that 20 of 86 patients (23%) studied had a positive pH study, 33% of patients with any grade of esophagitis and 46% of these patients presented abnormal fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados relacionados aos sintomas no pós-operatório são compatíveis com os resultados encontrados em estudos anteriores, em adultos e em crianças e adolescentes, mostrando baixa correlação entre sintomatologia e achados endoscópicos (4,8,11,24,32) . Os sintomas de DRGE podem persistir ou recorrer mesmo sem anormalidades na válvula antirrefluxo, e pacientes com anormalidades relacionadas ao esôfago, como esofagite erosiva ou esôfago de Barrett, podem ser assintomáticos.…”
Section: Discussionunclassified
“…A proportion of patients have persistent reflux symptoms and require use of proton pump inhibitors despite normal functional studies (Eubancs et al 2000; Khajanchee et al 2002;Galvani et al 2003).…”
Section: Quality Of Life After Antireflux Surgerymentioning
confidence: 99%